Antibacterial Activity Of Jatropha Curcas Sap Against Staphylococcus Aureus - Abdulsalam, KhaLLeefah Almhdi; Abobaker, Abdelgani Mohamed; Bogdadi, Hamed Abdelsalam; Alezzawi, Mohamed Amar; Mohammed, Mohammed Omar Allafi (Journal of Neonatal Surgery, 2025)
Jatropha curcas is a plant that has long been known by the community as a border or hedge plant, a source of medicine, and a producer of oil for lamps. The sap plant contains various chemical compounds, including flavonoids, tannins, saponins, and jatrophine, which also show antibacterial and antifungal activity. One of the common bacteria in the human body is Staphylococcus aureus, which is associated with pyogenic infections, especially those that attack the skin. Staphylococcus aureus is one of the most common infectious agents, which enters the skin through hair follicles, sweat glands, or small wounds. The purpose of this study was to investigate the effect of Jatropha curcas L. on the growth of Staphylococcus aureus bacteria. This study was designed as a true experimental study, which aims to determine the symptoms or effects resulting from certain treatments. Preparation of Jatropha curcas L. sap with a concentration of 25% v/v. Required 025 ml of Jatropha curcas L. sap with a concentration of 100% v/v and 0.75 ml of sterile distilled water. Preparation of Jatropha curcas L. sap with a concentration of 50% v/v. Required 0.5 ml of Jatropha curcas L. sap with a concentration of 100% w/v and 0.5 ml of sterile distilled water. Preparation of Jatropha curcas L. sap with a concentration of 75% v/v. Required 0.75 ml of Jatropha curcas L. sap with a concentration of 100% w/v and 0.25 ml of sterile distilled water. The results showed that the 25% concentration of J. curcas sap had an inhibition zone of 21.75 mm, the 50% concentration had an inhibition zone of 22.63 mm, the 75% concentration had an inhibition zone diameter of 24.13 mm, and the 100% concentration had an inhibition zone diameter of 24.75 mm. The conclusion showed that the higher the concentration of Jatropha curcas sap, the larger the diameter of the inhibition zone, this indicates a significant effect on the growth of Staphylococcus aureus bacteria.